Mapping the Evolution of Code-Based Cryptosystems: A Comprehensive Analysis Using Science Mapping Techniques - Ritu Redhu; Ekta Narwal (Contemporary Perspective on Science, Technology and Research Vol. 6, 2024)
In this chapter, we provide a comprehensive overview of current state-of-the-art in code-based cryptosystems, including various error-correcting codes. The ACM Digital Library, IEEE Xplore, and Scopus databases are thoroughly searched to find relevant research articles. In this study, science mapping techniques are used to define thematic clusters, cited authors, and cited references that are important in shaping the evolving landscape of code-based cryptosystems that are based on error-correcting codes. The chapter finds future research areas and development, including improving polar code cryptosystem security and reliability. The issues such as finding an efficient public key algorithm and the trade-off between their security and performance are being identified by using this analysis. Thus, this survey provides researchers with a deeper understanding of interconnected knowledge domains, identifies emerging themes, and provides insight into code-based cryptosystems.